LAPAROSCOPIC ASSISTED APPENDECTOMY IN CHILDREN. OUR EXPERIENCE OF FIRST 50 CASES AT TERTIARY CARE HOSPITAL RAWALPINDI: Laparoscopic Assisted Appendectomy in Children - Ahmed, Waqas; Ahmed, Iftikhar; Ibrahim, Taseer; Awan, Safdar Hussain; Fraz, Omer; Safdar, Chaudhary Aqeel (Pakistan Armed Forces Medical Journal, 2018)
Objective: To present an experience of the first 50 cases of appendectomy performed via laparoscopy assistedopen technique.Study Design: Descriptive case series.Place and Duration of Study: This study was carried out at Pediatric Surgery department, Pak Emirates MilitaryHospital Rawalpindi, from Jan 2016 to Apr 2018.Material and Methods: Fifty patients (